2015
DOI: 10.1051/0004-6361/201425019
|View full text |Cite
|
Sign up to set email alerts
|

The Seven Sisters DANCe

Abstract: Context. The DANCe survey provides photometric and astrometric (position and proper motion) measurements for approximately 2 million unique sources in a region encompassing ∼80 deg 2 centered on the Pleiades cluster. Aims. We aim at deriving a complete census of the Pleiades and measure the mass and luminosity functions of the cluster. Methods. Using the probabilistic selection method previously described, we identified high probability members in the DANCe (i ≥ 14 mag) and Tycho-2 (V 12 mag) catalogues and st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(158 citation statements)
references
References 41 publications
11
146
1
Order By: Relevance
“…We chose objects in our search to the right of the dashed line (using an earlier, preliminary version of y P1 photometry); J−H was not used to select objects. Our discoveries have normal -y J Bouy et al (2015) measurement is more precise. The adopted proper motion is very similar to PSOJ077.1+24 and consistent with our mean Taurus proper motion.…”
Section: Proper Motionsmentioning
confidence: 52%
See 1 more Smart Citation
“…We chose objects in our search to the right of the dashed line (using an earlier, preliminary version of y P1 photometry); J−H was not used to select objects. Our discoveries have normal -y J Bouy et al (2015) measurement is more precise. The adopted proper motion is very similar to PSOJ077.1+24 and consistent with our mean Taurus proper motion.…”
Section: Proper Motionsmentioning
confidence: 52%
“…We show their locations in the sky in Figure 2. PSOJ060.3+25 was previously identified by Sarro et al (2014) and Bouy et al (2015) as a likely very low-mass member of the Pleiades cluster, based on photometry and astrometry. PSOJ237.1471−23.1489 (hereinafter PSO J237.1 −23) was identified by Lodieu (2013) as a photometric and astrometric candidate member of Upper Sco.…”
Section: Ultracool Discoveriesmentioning
confidence: 99%
“…There is an extraordinary amount of works devoted to the Pleiades in the literature but, despite this fact, new cluster members have been uncovered (Sarro et al 2014;Bouy et al 2015). Figure 29, taken from Bouy et al (2015), displays the HRD for the Pleiades.…”
Section: The Cornerstone: the Pleiadesmentioning
confidence: 99%
“…Figure 29, taken from Bouy et al (2015), displays the HRD for the Pleiades. The original caption says: "Hertzsprung-Russell diagram of the Pleiades (black dots) with the Allard (2014) (red), Bressan et al (2012) (light green) and Siess et al (2000) (light blue) models, as well as Praesepe's sequence as reported in Kraus & Hillenbrand (2007) (green)."…”
Section: The Cornerstone: the Pleiadesmentioning
confidence: 99%
See 1 more Smart Citation